PEMBERDAYAAN ANGGOTA PMR DALAM PERTOLONGAN PERTAMA CEDERA OLAHRAGA (METODE PEACE DAN LOVE) DI SMAN 1 GURAH - Zakiyyatul Fuadah, Dina (STIKES dan AKZI Karya Husada Kediri, 2023)
First aid for injuries suffered by upper middle school students is important to prevent the risk of harm due to injury. One of them in sports injuries can be given proper injury first aid management training. The purpose of this community service is to determine the ability of cadres and their members in carrying out sports injury first aid with the Peace&love method. Method of empowering cadres with lectures and demonstrations, The sample of 20 students consisted of 5 PMR cadres. There are 15 students. The sample is expected to be able to continue the Peace&Love method of sports injury first aid throughout the PMR population. Community service instruments use observation sheets. The results of the analysis before intervention were average (50%) abilities in the less category, after intervention almost respondent (75%) abilities in the good category. This means that cadres and PMR members have increased sports injury first aid ability scores. The Peace&Love method is more interesting, easy to apply, effective and more understanding for respondents. We recommend that the first aid ability of sports injuries with the Peace&Love method be used in everyday life.